Vitamin A deficiency and association between serum retinol and IGF-1 concentrations in Brazilian children with Down syndrome - Ivan Savioli Ferraz; Débora Mônica Costa Vieira; Luiz Antonio Del Ciampo, Jr; Fábio da Veiga Ued; Ane Cristina Fayão Almeida; Alceu Afonso Jordão, Jr; Davi Casale Aragon; Edson Zangiacomi Martinez; Carlos Eduardo Martinelli, Jr; Carlos Alberto Nogueira- (Elsevier, 2022)
Objective: To determine the prevalence of vitamin A deficiency (VAD) and serum concentrations of retinol, correlating them with IGF-1 concentrations in preschoolers with DS. Methods: Cross-sectional study was conducted on 47 children with DS aged 24 to 72 months, in Ribeirão Preto, Brazil. VAD was determined by the relative dose-response (RDR) test. Retinol serum concentration ≤ 0.70 µmol/L and IGF-1 serum concentration below the 3rd percentile for sex and age were considered to represent deficiency. C-reactive protein (CRP) was determined at the beginning of the study. Weight, height, and information about fever and/or diarrhea were obtained at the beginning of the study. Results: VAD prevalence was 25.5% (12/47), and 74.5% (35/47) of the children had deficient retinol before the intervention. CRP was not associated with VAD. Mean IGF-1 were 103.5 ng/mL (SD = 913) for the group with VAD and 116.3 ng/mL (SD = 54.9) for the group with no VAD (p-value = 0.85); 8.5% (4/47) of the children showed deficient IGF-1, but without VAD. No association was observed between VAD and IGF-1 deficiency. A moderate positive correlation was observed between pre-intervention retinol and IGF-1 (ρ = 0.37; p-value = 0.01). Conclusion: a high prevalence of VAD and deficient retinol was observed and there was a positive correlation between serum retinol and IGF-1.